2012
DOI: 10.18227/1982-8470ragro.v6i2.706
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem da proteção do solo por plantas de cobertura no sul de Minas Gerais.

Abstract: Resumo -A cobertura do solo é o fator de maior importância relativa no controle da erosão hídrica. Assim, objetivou-se no presente estudo elaborar a modelagem da cobertura vegetal de vinte e quatro plantas de cobertura, em diversos sistemas de plantio e históricos de uso, com potencial para cultivo no Sul de Minas Gerais. Para avaliação da cobertura vegetal foram realizadas avaliações no campo utilizando uma régua de classificação da cobertura vegetal, sendo o delineamento experimental inteiramente casualizado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…When simulating conservationist management techniques for agropastoral activities at the hydrographic sub-basin, Ayer et al (2015) found out that total contribution of erosion in pasture plots and eucalyptus plantations decreases to 8.50% and 0.20%, respectively. This illustrates the potential and advantages of agro ecological conservationist management techniques, as illustrated by Freitas et al (2012).…”
Section: Resultsmentioning
confidence: 76%
“…When simulating conservationist management techniques for agropastoral activities at the hydrographic sub-basin, Ayer et al (2015) found out that total contribution of erosion in pasture plots and eucalyptus plantations decreases to 8.50% and 0.20%, respectively. This illustrates the potential and advantages of agro ecological conservationist management techniques, as illustrated by Freitas et al (2012).…”
Section: Resultsmentioning
confidence: 76%
“…The SCI values corroborate with Castro et al (2011), who studied several cover crops, including jack bean. Freitas et al (2012) and Dias et al (2013) found that cultivation of jack bean reduced soil, water, nutrient, and soil organic matter losses, and strongly recommending it as a soil cover crop for the Lavras region.…”
Section: Soil Cover Indexmentioning
confidence: 99%
“…Combining corn with cover crops has been an intercropping combination effective in improving soil physical properties, controlling water erosion, and reducing organic carbon, nutrient, soil, and water losses (Debarba and Amado, 1997;Spagnollo et al, 2001;Albuquerque et al, 2005;Gilles et al, 2009;Silveira and Stone, 2010;Chen and Weil, 2011;Gabriel and Quemada, 2011;Freitas et al, 2012;Pereira et al, 2016). The benefits of using cover plants were also demonstrated by Gómez et al (2011), who concluded that they significantly reduced water erosion in comparison to traditional tillage practices in Southern France, Spain, and Portugal.…”
Section: Introductionmentioning
confidence: 99%
“…Além das observações em campo, a importância relativa de cada fator foi atribuída com base na bibliografia. Para Weill e Sparovek (2008) e Freitas et al (2012) a cobertura do solo é o componente mais importante no controle da erosão hídrica. Nessa perspectiva, ao uso do solo foi atribuído maior peso, pois a alteração da cobertura vegetal é que rompe o estado de equilíbrio dinâmico e acelera os processos erosivos.…”
Section: Solounclassified